Komunikasi Simbolik dalam Menentukan Harga Perolehan Jabatan Kepala Desa di Madura - Ach. Baihaki (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2023)
This study aims to analyze the expenditure by using symbolic language as a proxy in election of head of village in Madura by using an interpretive qualitative method in order to enreach the meaning of the communication by the parties based on a cost accounting perspective, as identifying by the intention of the cost, as fix cost,variable cost, and semi variable cost. The results of the research point outed that there are many activities in the election of head of village process from before the nomination until the completion of the inauguration have cost dimension are nyaghêrêh, ekareng towa'ah, ghuruh, ajêgêh, angin tang ngin, tongket, and uniformity also in cigarret. The costs that must be incurred by the candidate as a fix cost and tend to be semi variable cost at the day of the election and also at the day of the inauguration. Some times the cost can continue until after becoming a village head. The variable cost are usually in order to influence voter decision from before voting day to the voting day.